Pengujian Perangkat Lunak Berstandar ISO/IEC 29119 pada Aplikasi Sistem Absensi “SIKARYAWAN” Berbasis Website - Putra Zahwa Pratama; Achmad Febriyadi; Chairul Anwar (OKTAL : Jurnal Ilmu Komputer dan Sains, 2025)
The development of web-based attendance systems requires functional quality assurance to ensure that employee attendance data is recorded accurately and transparently. This study aims to evaluate the quality of the "SIKARYAWAN" attendance system application by referring to the ISO/IEC 29119 international standard through the Software Testing Life Cycle (STLC) approach. The testing method employed is Black Box Testing to validate core features such as user authentication, attendance recording, leave submission, and data recapitulation. This research refers to 12 related literatures, including the implementation of ISO 29119 in various information systems and efficient functional testing techniques. The results indicate that the SIKARYAWAN application has met the users' functional requirements, although several improvements in input validation are noted to minimize errors. The application of the ISO/IEC 29119 standard in this study successfully provides structured testing documentation and enhances confidence in the quality of the attendance information system.